2016
DOI: 10.1002/1873-3468.12425
|View full text |Cite
|
Sign up to set email alerts
|

Structural similarities and differences in H‐NS family proteins revealed by the N‐terminal structure of TurB in Pseudomonas putida KT2440

Abstract: H-NS family proteins play key roles in bacterial nucleoid compaction and global transcription. MvaT homologues in Pseudomonas have almost negligible amino acid sequence identity with H-NS, but can complement an hns-related phenotype of Escherichia coli. Here, we report the crystal structure of the N-terminal dimerization/oligomerization domain of TurB, an MvaT homologue in Pseudomonas putida KT2440. Our data identify two dimerization sites; the structure of the central dimerization site is almost the same as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…1b; S1). The crystal structure of the TurB N-terminal domain (1- 61) has revealed that site 1 is formed by a “coiled-coil motif” between the N-terminal helices α1 (corresponding to H-NS α3) of two monomers 39 (fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1b; S1). The crystal structure of the TurB N-terminal domain (1- 61) has revealed that site 1 is formed by a “coiled-coil motif” between the N-terminal helices α1 (corresponding to H-NS α3) of two monomers 39 (fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…1a,b). This site is also formed by hydrophobic interactions between two α-helices (α4 and α2 for the long and short members, respectively) and stabilised by salt bridges 31, 39 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, preference of target DNA sequences of MvaT in P. aeruginosa [25] and the structure of dimerization/oligomerization domain of TurB [33] were reported. We are now performing kinetic studies on the DNA-protein and protein-protein binding properties of TurA, TurB, and Pmr.…”
Section: Discussionmentioning
confidence: 99%